KORUPSI - Dwi Maria Handayani (Pengarah: Jurnal Teologi Kristen, 2019)
Corruption is a classic problem in Indonesian. Many books and articles have addressed this issue, but there is very little from a biblical perspective. Corruption has occurred since the days of ancient Egypt and the practice of corruption is strongly associated with the practice of idolatry that was popular in that era. Israel, influenced by neighboring nations, is not immune to corruption and idolatry. Therefore the Old Testament law and the prophets proclaimed criticism and warning against the corruptors. The church today needs to develop anti-corruption teaching and re-establish its prophetic role in the midst of corrupt society.